Highly Diastereoselective Synthesis of Cyclopentenones via a One-Pot Gold Catalysis, Nazarov Cyclization and Alkylation Cascade - Liu, Meng-Qi; Zhou, Ai-Hua; Jiang, Shuang; Wang, Jia-Qi; Ye, Long-Wu (Synthesis, 2014)
Starting from readily available propargylic carboxylates, three sequential transformations [gold-catalyzed tandem reaction, scandium(III) trifluoromethanesulfonate catalyzed Nazarov cyclization, alkylation reaction] in a one-pot process led to the formation of cyclopentenone derivatives in excellent diastereoselectivities and moderate to good overall yields.
Keywords: gold catalysis; Nazarov cyclization; alkylation reaction; one-pot cascade; Lewis acids